An Exploration of Teachers' Perspectives on the Imbalance in Science and Social Studies Track Selection at SMAN 1 Mataram - Putri, Anggraini Purnama; Ningsih, Dewi Puspita; Apriawan, Andika; Rahmadi, Didin Septa (Global Journal of Social Learning, 2025)
The phenomenon of imbalance in the selection of Science (IPA) and Social Science (IPS) streams at the senior high school level remains a relevant issue in the context of Indonesian education. This study aims to explore teachers’ perspectives on the predominant tendency of students to choose the IPA stream at SMAN 1 Mataram, as well as the impacts of this imbalance on both teachers and the social dynamics among students. Using a qualitative approach with a case study method, data were collected through in-depth interviews with several teachers from diverse subject backgrounds. The findings indicate that the stream selection process is conducted objectively by considering academic achievement, psychological test results, as well as students’ interests and talents. However, student choices remain dominated by the IPA stream due to rational considerations related to future prospects. This imbalance affects the distribution of teachers’ workload and creates distinct social characteristics between the streams, although it does not cause overt conflicts. These results highlight the importance of fairer stream socialization and the critical role of teachers in providing personalized guidance to students. This study recommends strengthening internal school policies to manage the imbalance and encourages further research exploring students’ perspectives and other socio-cultural variables influencing stream selection.